Mechanisms of Innate Neuroprotection - Giuseppe Pignataro (Frontiers Media SA, 2016)
As clinical trials of pharmacological neuroprotective strategies in stroke have been disappointing, attention has turned to the brain's own endogenous strategies for neuroprotection. Two endogenous mechanisms have been recently characterized, ischemic preconditioning and ischemic postconditioning. In the present topic newly characterized mechanisms involved in preconditioning- and postconditioning- neuroprotection will be discussed. The understanding of the mechanisms involved in the neuroprotective pathways induced by preconditioning and postconditioning will be clinically relevant for identifying new druggable target for neurodegenerative disorder therapy. Furthermore, the importance of these neuroprotective strategies resides in that it might be easily translatable into clinical practice. Therefore, the data presented here will highlight the capacity of ischemic preconditioning and postconditioning to be of benefit to humans.
English
Keywords: Neuroprotection; postconditioning; NCX; Stroke; seizure; miRNA; Alzheimer; preconditioning